ANALISIS TINGKAT KEPUASAN PELANGGAN SHOPEE TERHADAP E-SERVICE QUALITY DI KOTA PEKANBARU - Dewi, Sartika; Taufiqurrahman, Taufiqurrahman; Rendra, Wasnury (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
This study aims to analyze the level of customer satisfaction with the e-ServiceQuality provided by Shopee and to find out which Shopee service attributes needto be prioritized to improve and meet customer satisfaction. The variables used inthis study are the dimensions of e-Service Quality, which consist of; efficiency,system availability, fulfillment, privacy, responsiveness, compensation, andcontacts. The method chosen in this research is the Customer Satisfaction Index(CSI) method, the e-Service Quality method, and the Importance PerformanceAnalysis (IPA) method. This research was conducted on Shopee users who live inPekanbaru City, with a total sample of 120 respondents using a purposivesampling method. Testing and data processing was carried out with the help ofSPSS 21 and Ms. Excel. The results showed that the overall Shopee customersatisfaction index in Pekanbaru City based on the CSI calculation was "satisfied"with a value of 72.97%. Based on the overall e-Servqual calculation -0.32, whichmeans that the service quality from Shopee as a whole is not maximized. Based onthe results of the IPA calculation, 3 attributes need to be prioritized forimprovement or improvement (quadrant I). 10 attributes that need to bemaintained (quadrant II), 10 attributes that have low priority by the user(quadrant III), and 1 attribute that can be removed (quadrant IV). Keywords: Customer Satisfaction, e-Service Quality, Customer Satisfaction Index(CSI), Importance Performance Analysis (IPA)